Doing Historical Research in Museum and Digital Museum - M. Ma'ruf Misbah; Faizal Arifin (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This article discusses the role of museums and digital museums as scientific research destinations in history. Not only physical visits to museums but the Covid-19 pandemic has also accelerated the transformation of scientific destinations through digital museums. This study aimed to identify the role and contribution of the museum and digital museum as a destination for historical researchers to carry out scientific research activities in the field of history by analyzing material culture as a historical source collected by the museum. The Rijksmuseum is an example of a digital museum provider that provides a huge collection of museums for historical research. This article used qualitative research methods with historical science approaches, especially historical research methods, archaeological approaches, and sociocultural approaches. The results indicate that there are opportunities for historical researchers to write history comprehensively, which are not only based on historical sources in oral and written form but can also be supplemented with historical information obtained from analysis of historical sources in the form of material culture which is a legacy from the past collected by the museum and digital museum. Thus, it appears that the museum which collects material culture has a significant role significant research destination in the field of history. As an impact of the existence of this material culture, historical researchers can obtain historical information from the analysis of that material culture to complement historical information obtained from the analysis of historical sources in other forms.Artikel ini membahas tentang peran museum sebagai tujuan penelitian ilmiah di bidang sejarah. Bukan hanya kunjungan fisik ke museum, pandemi Covid-19, mempercepat transformasi destinasi ilmiah sejarah melalui museum digital. Tujuan dari penelitian ini adalah untuk mengidentifikasi peran dan kontribusi museum serta museum digital sebagai tujuan peneliti sejarah untuk melakukan kegiatan penelitian ilmiah di bidang sejarah dengan menganalisis budaya material sebagai sumber sejarah yang dikumpulkan oleh museum. Rijksmuseum merupakan contoh penyedia digital museum yang menyajikan banyak koleksi museum bagi penelitian sejarah. Artikel ini menggunakan metode penelitian kualitatif dengan pendekatan ilmu sejarah, khususnya mengenai metode penelitian sejarah, pendekatan arkeologi, dan pendekatan sosiokultural. Hasil penelitian menunjukkan bahwa terdapat peluang bagi peneliti sejarah untuk menulis sejarah secara komprehensif, yang tidak hanya didasarkan pada sumber sejarah dalam bentuk lisan dan tulisan tetapi juga dapat dilengkapi dengan informasi sejarah yang diperoleh dari analisis sumber sejarah berupa kebudayaan material yang warisan dari masa lalu yang dikumpulkan oleh museum. Dengan demikian, tampak bahwa museum yang mengkoleksi material memiliki peran yang signifikan sebagai tujuan penelitian di bidang sejarah. Sebagai dampak dari keberadaan kebudayaan material ini, peneliti sejarah dapat memperoleh informasi sejarah dari analisis budaya material tersebut untuk melengkapi informasi sejarah yang diperoleh dari analisis sumber sejarah dalam bentuk lain.